The L730V/I RET roof mutations display different activities toward pralsetinib and selpercatinib - Tao Shen (Nature Portfolio, 2021)
Abstract Recently Food and Drug Administration (FDA)-approved pralsetinib (BLU-667) and selpercatinib (LOXO-292) are RET-selective protein tyrosine kinase inhibitors for treating RET-altered cancers, but whether they have distinct activity was unknown. The L730V/I mutations at the roof of the solvent-front site of the RET kinase were identified as strongly resistant to pralsetinib but not to selpercatinib. Selpercatinib effectively inhibited these mutants and the KIF5B-RET(L730V/I) oncogene-driven tumors.